Root-shoot characteristics, yield and economics of mungbean (Vigna radiata L.) under variable rates of phosphorus and nitrogen (Bangladesh Journal of Botany, 2020)
A field experiment was conducted to study the effect of nitrogen (N) and phosphorus (P) nutrition on growth, yield, economics, production efficiency (PE) and monetary efficiency (ME) of mungbean. Application of 55 kg N/ha caused improvement in root- and shoot-dry weight, leaf area index and biological yield. However, 40 kg N/ha recorded the highest pod length (8.2 cm), grains/plant (284), grain yield (2.1 t/ha), harvest index (29.4%), net returns (1,28,651 AFN/ha), benefit: cost ratio (2.6), PE (24 kg/ha/day) and ME (1,429 AFN/ha/day). Use of 60 kg P2O5 /ha resulted in the highest pod length (8.3 cm), seeds/plant (285), grain yield (2.0 t/ha), harvest index (30.5%), net returns (1,161,22.9 AFN/ha), benefit: cost ratio (2.4), PE (22.4 kg/ha/day) and ME (1,290 AFN/ha/day). The combination of 40 kg N/ha and 60 kg P2O5 /ha recorded the highest yield, net returns, benefit: cost ratio, PE and ME. Hence, mungbean grown field should be treated with 40 kg N/ha and 60 kg P2O5/ha fertilizers for its higher productivity and profitability.